FORÇAS ARMADAS, URNAS ELETRÔNICAS E O PARADOXO DO IDEAL POPPERIANO DE SOCIEDADE ABERTA (Reflection and Critique Law Magazine, 2024)
Legal and philosophical research that explores two facts that occurred in the Brazilian political scene and proceeds to theoretical reflection, in the light of the concept of open society built by the philosopher Karl Popper, to find out if they would be protected by the Democratic State of Law. The text concludes that, although the actions can be characterized as enemies of the open society, there is no clear legal-dogmatic solution to this problem, which can be a risk for Brazilian democracy.